Factors influencing career success of women managers in Malaysian public sector - Abdul Manaf, Saidatul Hizam (2015)
Increasing opportunities for higher education resulted from strong economic condition placed more women in the professional and management fields in Malaysia. But less number of women managers securing higher management post were still an issue in the Malaysian Public Sector especially in Administrative and Diplomatic Service (ADS). Several factors were identified in previous literature as an explanation to lack of women’s career success such as personal abilities, motivation and work environment but there was still no model fit to explain the phenomenon especially in different cultural setting. Besides that, women also tend to define career success differently from hat of men. Subjective career success was a matter of importance to women in defining their career success. Therefore, the aim of this study is to investigate the level of women managers objective and subjective career success and the relationship between the selected independent variables and women’s objective (monthly gross income) and subjective career success (career satisfaction). This cross-sectional correlational study was conducted on 128 women managers in Administrative and Diplomatic Service (ADS) in 12 ministries in Putrajaya. A quantitative survey was designed using self-administered questionnaire. The study used Social Cognitive Career Theory (SCCT) which stressed the importance of individual and environmental factors in career performance from which it derived its theoretical framework. Three groups of variables were identified in predicting women managers’ objective and subjective career success; i) individual related variables (self-efficacy, proactive personality and extraversion), ii) human capital variables (work experience and sense of competence) and iii) organizational related variables (organizational culture and perceived organizational justice). The findings of this study revealed that individual, human capital and organizational factors have significant effect on women managers’ objective and subjective career success. Two Individual factors; self-efficacy and proactive personality were found positively related to objective and subjective career success. Human capital factors such as work experience were highly correlated to objective career success whereas sense of competence was positively correlated to both objective and subjective career success. Women managers’ subjective career success were found to be positively correlated with organizational factors such as organizational culture and organizational justice. Result of the regression model revealed that the best predictors for objective career success of women managers were work experience and self-efficacy whereas self-efficacy and perceived organizational justice were the significant predictors of women managers’ subjective career success. The study suggested some recommendations that women managers should be given more opportunities in developing their careers through appropriate training and exposure in different job skills which then develop their self-efficacy and sense of competence. This would increase their capabilities and give more chances of being selected to higher management post in an organization. HRD practitioners should pay more attention to eliminate bias and unfair treatment in organizational practices because justice perception among employees would affect their career performance and job satisfaction. The study has some limitations as it was conducted among women managers in the public sector organizations. Future studies may involve women managers in private organizations to increase generalizability of the study.